Everything Is Diagrammatic (KULT_online, 2011)
Diagrammatology is booming. However, current research is insufficient, because diagrammatology is more than just the study of diagrams, as Matthias Bauer and Christoph Ernst argue in their introductory book. Drawing on Charles Sanders Peirce’s semiotics, they show how diagrammatology becomes, in effect, the study of all processes of understanding and knowledge operating at the intersection of the mind and physically embodied signs. The authors show that this conception opens up valuable new vistas for linguistics and art history as well as for literary, film, and media studies. However, when arguing for the wide applicability of Peirce’s concept, they lose sight of the differences between the diagrammatic operations discussed, and the limits of diagrammatology.